2000
DOI: 10.1524/ract.2000.88.6.335
|View full text |Cite
|
Sign up to set email alerts
|

Trivalent lanthanide and actinide extraction by calixarenes with different ring sizes and different molecular flexibility

Abstract: The binding properties of [1 n ]metacyclophanebased cation exchangers (n ϭ 5, 6, 7) towards trivalent lanthanides and americium were investigated by means of solvent extraction from water to chloroform and xylene. Extraction constants for four ligands were calculated for Ln(III) and Am(III). Three of the ligands lack Bu t groups in 4-position, giving them higher molecular flexibility compared with the corresponding t-butylcalixarenes. Due to this reason, changing the cavity size lead to small changes in metal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…For this, we first checked the solubility table given in the literature 15 . Due to the relative insolubility of the p-tert-butylcalix [6] and [8]arenes in hexane, it seemed judicious to us to treat the crude mixture in boiling hexane. Several tests allow us to optimize the mass concentration of crude (60 g/L) as well as the duration of the treatment (4 hours reflux).…”
Section: Fig 3 Conversion Rates In P-tert-butylcalixmentioning
confidence: 99%
See 4 more Smart Citations
“…For this, we first checked the solubility table given in the literature 15 . Due to the relative insolubility of the p-tert-butylcalix [6] and [8]arenes in hexane, it seemed judicious to us to treat the crude mixture in boiling hexane. Several tests allow us to optimize the mass concentration of crude (60 g/L) as well as the duration of the treatment (4 hours reflux).…”
Section: Fig 3 Conversion Rates In P-tert-butylcalixmentioning
confidence: 99%
“…Once the solution cold, a precipitate (P1) was separated by filtration from the mother liquors which was concentrated, leading to mixture B. The HPLC analysis of the precipitate and the mother liquors revealed that p-tertbutylcalix [6] and [8]arenes were removed from the crude mixture (Spectrum B, Fig. 4).…”
Section: Fig 3 Conversion Rates In P-tert-butylcalixmentioning
confidence: 99%
See 3 more Smart Citations